An Examination of Student Success within Canadian Higher Education: Fifty Years of Findings and Recommendations for the Future - Holmes, Jason R. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
This article explores the student success literature published within the Canadian Journal of Higher Education (CJHE) over the last fifty years. Sixty articles were thematically organized into seven component measures of student success to present consistent themes that have persisted within the CJHE from inception in 1971 to 2020. Analysis demonstrates that there has been a disproportionate interest in some aspects of student success such as post-college performance, while other areas such as educational attainment and student engagement have lagged considerably behind in focus. Scholars have presentedongoing concerns supported by a wide range of data regarding the underemployment of graduates from Arts and Humanities, the sparse professorial landscape and the underutilization of Canadian PhD graduates in the workforce, debate on student competence and skill measurement, and the lack of large data sets on student persistence. Results suggest that a continuous effort is required to understand and support student success in a variety of formats—both within the academy and out in the workforce. Thus, this article concludes with a discussion and recommendations for future research avenues in the field of academic success and various subfields that may be of interest to higher education scholars and those who support student success.